2000
DOI: 10.1074/jbc.275.6.4336
|View full text |Cite
|
Sign up to set email alerts
|

Activation of p70 Ribosomal Protein S6 Kinase Is an Essential Step in the DNA Damage-dependent Signaling Pathway Responsible for the Ultraviolet B-mediated Increase in Interstitial Collagenase (MMP-1) and Stromelysin-1 (MMP-3) Protein Levels in Human Dermal Fibroblasts

Abstract: Ultraviolet B (UVB) irradiation has been shown to stimulate the expression of matrix-degrading metalloproteinases via generation of DNA damage and/or reactive oxygen species. Matrix-degrading metalloproteinases promote UVB-triggered detrimental long term effects like cancer formation and premature skin aging. Here, we were interested in identifying components of the signal transduction pathway that causally link UVBmediated DNA damage and induction of matrix-degrading metalloproteinase (MMP)-1/interstitial col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
76
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 84 publications
2
76
0
Order By: Relevance
“…We also found that both ribosomal protein S6 and an S6 kinase are phosphorylated after UV-B exposure. Phosphorylation of these proteins is activated by UV-B in some types of cultured animal cells (Brenneisen et al, 2000;Nomura et al, 2001) where S6 phosphorylation has been implicated in the translational up-regulation of mRNAs containing the 5# TOP motif; exemplar transcripts encode components of the protein synthetic apparatus (Thomas, 2002). One mechanism permitting selective translation of eukaryotic mRNA requires an oligopyrimidine tract at the 5# terminus.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We also found that both ribosomal protein S6 and an S6 kinase are phosphorylated after UV-B exposure. Phosphorylation of these proteins is activated by UV-B in some types of cultured animal cells (Brenneisen et al, 2000;Nomura et al, 2001) where S6 phosphorylation has been implicated in the translational up-regulation of mRNAs containing the 5# TOP motif; exemplar transcripts encode components of the protein synthetic apparatus (Thomas, 2002). One mechanism permitting selective translation of eukaryotic mRNA requires an oligopyrimidine tract at the 5# terminus.…”
Section: Discussionmentioning
confidence: 99%
“…An increased translation of mRNAs encoding ribosomal proteins and translation factors has been suggested as an additional mechanism for recovery from ribosome damage in animal cells (Meyuhas et al, 1997;Brenneisen et al, 2000). Previously, phosphorylation of the 40S ribosomal protein S6 has been implicated in the translational up-regulation of mRNAs coding for the components of protein synthetic apparatus in specific cultured cell types (Thomas, 2002).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…UV light exposure initially stimulates S6K activity and within the first half an hour to 7 h after which it decreases and reaches background levels. The stimulating effect upon UV exposure on S6K activity is rapamycin sensitive (Parrott and Templeton, 1999;Brenneisen et al, 2000;Ding et al, 2002;Huang et al, 2002). Interestingly, additional pathways (p38, ERK1/2, JNK and PI3K) may also affect S6K phosphorylation (Zhang et al, 2001).…”
Section: Ultraviolet and Rosmentioning
confidence: 99%